Sistem Pendukung Keputusan Penilaian Kinerja Guru Pada Sekolah Dasar Negeri 1 Ambarawa Menggunakan Metode Topsis - Satrio Wibowo, Andi (YHMM PUBLISHING, 2024)
Teacher performance evaluation is a crucial aspect of improving the quality of education in schools. However, manual assessment processes often face challenges such as subjectivity, inconsistency, and lack of transparency in decision-making. To address these issues, this study aims to design and develop a Decision Support System (DSS) using the Technique for Order of Preference by Similarity to Ideal Solution (TOPSIS) method to assist the school in evaluating teacher performance in an objective and structured manner. The TOPSIS method is chosen for its ability to rank alternatives based on their closeness to the ideal positive and negative solutions, thus supporting more rational decision-making. The evaluation criteria include discipline, pedagogical competence, responsibility, teamwork, and innovation in teaching. The system is implemented as a web-based application accessible to school management. Testing results show that the system can provide accurate, consistent, and data-driven performance evaluations. This system is expected to make.